Threshold Behavior for Second Initial Boundary Value Problem of F-N Equations (Journal of Partial Differential Equations, 1991)
Under biologically reasonable assumptions the threshold behavior for second initial boundary value problem of F-N equation is proved.
Keywords: Threshold behavior; coupled system; second initial boundary value problem